DC-SIGNR, a DC-SIGN homologue expressed in endothelial cells, binds to human and simian immunodeficiency viruses and activates infection in trans - Pöhlmann, Stefan (The National Academy of Sciences, 2001)
DC-SIGN, a C-type lectin expressed on the surface of dendritic cells (DCs), efficiently binds and transmits HIVs and simian immunodeficiency viruses to susceptible cells in trans. A DC-SIGN homologue, termed DC-SIGNR, has recently been described. Herein we show that DC-SIGNR, like DC-SIGN, can bind to multiple strains of HIV-1, HIV-2, and simian immunodeficiency virus and transmit these viruses to both T cell lines and human peripheral blood mononuclear cells. Binding of virus to DC-SIGNR was dependent on carbohydrate recognition. Immunostaining with a DC-SIGNR-specific antiserum showed that DC-SIGNR was expressed on sinusoidal endothelial cells in the liver and on endothelial cells in lymph node sinuses and placental villi. The presence of this efficient virus attachment factor on multiple endothelial cell types indicates that DC-SIGNR could play a role in the vertical transmission of primate lentiviruses, in the enabling of HIV to traverse the capillary endothelium in some organs, and in the presentation of virus to CD4-positive cells in multiple locations including lymph nodes.